2014
DOI: 10.1039/c4fo00229f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DHA on plasma fatty acid availability and oxidative stress during training season and football exercise

Abstract: The aim was to determine the effects of a diet supplemented with 1.14 g per day of docosahexaenoic acid (DHA) for eight weeks on the plasma oxidative balance and anti-inflammatory markers after training and acute exercise. Fifteen volunteer male football players were randomly assigned to placebo or experimental and supplemented groups. Blood samples were taken under resting conditions at the beginning and after eight weeks of training under resting and post-exercise conditions. The experimental beverage increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Erythrocyte and beverage fatty acids were extracted in duplicate with chloroform/methanol (2:1 v/v) by a modified method of Folch [12,34], containing 0.01% butylated hydroxyanisole as antioxidant and 20 µL of n-heptadecanoic acid (15 mM) as the internal standard. The resultant organic phase was evaporated under a nitrogen stream at 55 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Erythrocyte and beverage fatty acids were extracted in duplicate with chloroform/methanol (2:1 v/v) by a modified method of Folch [12,34], containing 0.01% butylated hydroxyanisole as antioxidant and 20 µL of n-heptadecanoic acid (15 mM) as the internal standard. The resultant organic phase was evaporated under a nitrogen stream at 55 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The increased IL-6 plasma levels after exercise results from muscular secretion and exerts an anti-inflammatory action [23,24]. In turn, increased PGE2 after exercise could also be considered an anti-inflammatory effector [12,54]. TNFα is considered a pro-inflammatory cytokine that increases in plasma as result of dietary functional beverage supplementation and as result of exercise in senior athletes, in any event.…”
Section: Effects On Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand McAnulty et al [85] showed that supplementation with n-3 PUFA (2.4 g/day), versus placebo (soybean oil) in trained cyclists resulted in a greater post-exercise plasma concentration of F2-isoprostanes following three days of 3-hour cycling sessions. In addition, there are studies which find no effect of n-3 PUFA supplementation on exercise induce markers of oxidative stress [86], [87]. A great deal of the confusion in this area likely relates to the many different participant groups, exercise protocols and chosen marker/markers (and analytical techniques) of oxidative stress.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Supplementation of FAs, including omega-3 polyunsaturated FAs (n-3 PUFAs) and extra virgin olive oil (EVOO), are consumed to reduce levels of inflammation [38,39], however, the impact of these supplements on exercise-induced inflammation is equivocal. Some studies have detected reductions in inflammation post-exercise with FA supplementation [40,41], whereas, others have reported no change in inflammation [42,43]. An emerging mechanism for the anti-inflammatory impact of FA supplementation is via epigenetic modifications [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%